Formal vs. informal institutional distances and the competitive advantage of foreign subsidiaries in Latin America - Henrique Correa da Cunha; Mohamed Amal; James Mark Viminitz (Economies, 2022)
By focusing on the tacit and explicit characteristics of informal and formal institutional distances, this study investigates the competitive advantage of foreign subsidiary firms from developed countries and emerging markets operating in Latin America. Following recent research on distances in international management, this study measured the size and direction of distances and computed formal institutional distances based on the world governance indicators from the World Bank, whereas informal institutional distances are calculated using the four original dimensions of Hofstede. Considering that culture is tacit, whereas formal institutions are explicit, it is argued that these differences affect the ability to convert experience dealing with cultural and formal institutional conditions in the home country into firm specific advantages (FSAs) in a foreign host country. These assumptions are tested quantitatively using data from the Orbis database, a sample that includes over 4200 firm-year observations covering 10 of the largest economies in Latin America. In a departure from previous studies investigating the implications of FID direction, it is shown that the effects in specific directions are different for foreign subsidiaries from developed countries and from emerging markets. The results reveal that emerging market firms are at an advantage when operating in less developed host countries, whereas foreign subsidiaries from developed countries can adjust more positively when operating in host countries with strong formal institutions. On the other hand, the effects of the different CD dimensions depend on the direction towards host countries with specific cultural profiles. These findings indicate that foreign subsidiaries from emerging markets have a clear advantage in dealing with institutional voids in Latin America (i.e., FID towards less developed host countries), whereas the effects of CD are the same for all firms. This suggests that the cultural profile of the host country is what really matters.
Keywords: 330; asymmetry; Latin America; cultural distance; direction of distance; foreign subsidiary performance; formal institutional distance; internationalization theory